The riddler : fantastic puzzles from FiveThirtyEight / edited by Oliver Roeder ; foreword by Nate Silver.: fantastic puzzles from FiveThirtyEight / edited by Oliver Roeder ; foreword by Nate Silver. (2018) - Unknown
No abstract available